The essential research curriculum for doctor of pharmacy degree programs – 2021. Issue 3 (2nd February 2022) - Karnes, Jason H.; Asempa, Tomefa; Barreto, Jason N.; Belcher, Rachel M.; Bissell, Brittany D.; Gammal, Roseann S.; Kier, Karen L.; Lee, Craig R.; Liu, Leanne; McCune, Jeannine S.; Minhaj, Faisal S.; Newsome, Andrea Sikora; et al.
Abstract: Training in the scientific method and research design in doctor of pharmacy (Pharm.D.) curricula enables critical thinking, acquisition of reliable information, rigorous evaluation of emerging literature, and application of evidence‐based medicine in practice. Although research skills are essential for clinical pharmacists and many professional societies recognize the critical need for research in the Pharm.D. curriculum, standardization regarding essential research curricular competencies and content is lacking. Consequently, research skill development is often de‐emphasized in pharmacy education in favor of clinical knowledge and skills. This update to the recommendations of the American College of Clinical Pharmacy's 2008‐2009 Task Force on Research in the Professional Curriculum is provided to meet the evolving needs of contemporary pharmacy practice. The update discusses the importance of research training for Pharm.D. students, proposes essential research competencies and curriculum content for Pharm.D. programs, and highlights several successful strategies for fostering research among Pharm.D. students. In particular, the update advocates enhanced adoption of minimum standards for research skill development across Pharm.D. programs and integration of advanced research competencies to support the development of Pharm.D.‐trained scientists.